RANCANG BANGUN APLIKASI E-BOOK PANDUAN MAINTENANCE KOMPUTER MENGGUNAKAN METODE TEXT TO SPEECH BERBASIS ANDROID - Velisia Wijaya; Syafri Arief; Ahyar Muawwal (KHARISMA Tech, 2019)
Problems with how to maintenance on a computer that is published by several publishers are generally in the form of prints. The purpose of this study was to design an android-based computer e-book maintenance application guide, and implement the TTS method on an android-based computer maintenance e-book guide application. This application is built on the Android operating system using the Java programming language, and prototyping methods. Data collection is done by collecting data from literature review. From the results of the implementation testing carried out from the five main menus it produces data in the form of sound, images, text, and videos from each trouble menu, so that this application can be used and well received as a solution to existing problems.